Drug Delivery Based on Nanoparticulate Systems - Kemal Çetin; Koray Şarkaya (Düzce Üniversitesi Bilim ve Teknoloji Dergisi)
The administration route of an active ingredient and the materials used to deliver it are as important as the synthesis of that active ingredient. For the treatment to be effective, the active ingredient must be present in the right amount and in the right place at the right time. Therefore, researchers have been studying a wide variety of drug delivery systems, taking into account the route of administration of the drug, its half-life, and its effective and toxic amounts. Because of its numerous benefits, nanotechnology has attracted attention in pharmaceutical research as well as many other fields. Nanoparticles have the potential to disperse hydrophobic drugs in an aqueous solution, deliver drugs to the targeted site, and thus selectively direct therapeutic agents such as antineoplastic drugs. This study provides a detailed discussion of the many inorganic, polymeric, and lipid-based nanoparticulate systems designed for drug delivery.